2014
DOI: 10.1111/ijag.12061
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass: An In‐Vitro Comparative Study of Doping with Nanoscale Copper and Silver Particles

Abstract: Bioactive glasses (BGs) based on 50SiO2‐45CaO‐5P2O5 system doped with 1, 5, and 10 mol% CuO or Ag2O were separately synthesized using quick alkali sol‐gel method. Scanning electron microscope (SEM) analysis of the samples confirmed the formation of nano‐sized BGs, whereas Fourier transform infrared (FTIR) spectra showed characteristic peaks for silica and phosphate groups. X‐ray diffraction (XRD) pattern of the heat‐treated (700°C) samples revealed the presence of crystalline metallic silver phase in all Ag‐do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 70 publications
7
87
1
Order By: Relevance
“…In another study, incorporation of Ag 2 O into a bioactive glass enabled antimicrobial properties without compromising its bioactivity [124]. Antibacterial surfaces are of particular interest for reducing biomaterial-centered infection and, thereby, enhancing tissue integration and bone regeneration [124,143,144].…”
Section: Biological Propertiesmentioning
confidence: 99%
“…In another study, incorporation of Ag 2 O into a bioactive glass enabled antimicrobial properties without compromising its bioactivity [124]. Antibacterial surfaces are of particular interest for reducing biomaterial-centered infection and, thereby, enhancing tissue integration and bone regeneration [124,143,144].…”
Section: Biological Propertiesmentioning
confidence: 99%
“…The studies have showed that Ag + ions have lower minimum inhibitory concentrations against bacteria including S. aureus and E. coli (MIC, 0.03‐8 vs 256‐448 μg/mL) and smaller Lethal doses 50 for L929 mouse fibroblast cells (LD50, 3.5×10 −3 vs 2.3×10 −1 mmol/L) than Cu 2+ ions . Fast initial release of Ag + ions from Ag‐doped bioactive glass makes it a better rapid bacteria‐killing agent than Cu‐doped glass …”
Section: Resultsmentioning
confidence: 99%
“…The Ag‐containing bioactive glass (Ag‐glass) powders were sol‐gel prepared and exhibited antibacterial activity; however, the structure and properties of sol‐gel prepared Ag‐glass coatings have rarely been studied . In this work, AgNO 3 was added into the SiO 2 ·CaO·P 2 O 5 sol, and the glass films containing different silver contents were dip coated on titanium substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several studies have shown proper antibacterial properties achieved by different formulations of bioactive glasses incorporating several oxides and the effects of biologically active ions on bone tissue engineering have been discussed in literature . In addition, commercial products based on bioactive glass (melt‐derived, composition SiO 2 53%, Na 2 O 23%, CaO 20%, P 2 O 5 4%) are being successfully applied in the clinic to treat osteomyelitis and the application of BGs to treat bone infections by the effect of pH increase is well demonstrated in literature .…”
Section: Organic Agents Incorporated Into Bioactive Glassmentioning
confidence: 99%